Contribution of physical education to overall physical activity. Issue 5 (12th December 2011) - Meyer, U.; Roth, R.; Zahner, L.; Gerber, M.; Puder, J. J.; Hebestreit, H.; Kriemler, S.
<x xml:space="preserve">Abstract</x> For many children, physical activity (PA) during physical education (PE) lessons provides an important opportunity for being physically active. Although PA during PE has been shown to be low, little is known about the contribution of PA during PE to overall PA. The aim was therefore to assess children's PA during PE and to determine the contribution of PE to overall PA with special focus on overweight children. Accelerometer measurements were done in 676 children (9.3 ± 2.1 years) over 4–7 days in 59 randomly selected classes. Moderate‐and‐vigorous PA (MVPA; ≥ 2000 counts/min) during PE (MVPAPE), overall MVPA per day (MVPADAY), and a comparison of days with and without PE were calculated by a regression model with gender, grade, and weight status (normal vs overweight) as fixed factors and class as a random factor. Children spent 32.8 ± 15.1% of PE time in MVPA. Weight status was not associated to MVPAPE. MVPAPE accounted for 16.8 ± 8.5% of MVPADAY, and 17.5 ± 8.2% in overweight children. All children were more active on days with PE than on days without PE (differences: 16.1 ± 29.0 min of MVPADAY; P ≤ 0.001; 13.7 ± 28.0 min for overweight children). Although MVPAPE was low, PE played a considerable role in providing PA and was not compensated by reducing extracurricular MVPA.